The Local Potential of "Kembang Island": A Contextual Study in Science Learning - Desy Purwasih; Insih Wilujeng (Vidya Karya, 2023)
Each region of Indonesia has a distinct characteristic that distinguishes it from the others. This distinctiveness has the potential to improve a region's economy. A region's local potential can be introduced through education by integrating local potential into learning, including science learning. In accordance with this, this study was conducted to analyze the concept of science based on the local potential of Kembang Island, to determine how to integrate the local potential of "Kembang Island" into science learning, and to determine the outcomes of the implementation of learning using local potential. The qualitative-descriptive study method was used. The instruments utilized for research were observation sheets and response questionnaires. The results indicate that Kembang Island's ecosystem material contains three scientific concepts: pollution, earth layers, and disasters. The fundamental competencies in the three materials are integrated into a webbed model with the theme "My Environment at Kembang Island Nature Park." The integration of local potential in learning took the form of lesson plans, student worksheets, handouts, and assessment instruments.